2006
DOI: 10.1002/mnfr.200500211
|View full text |Cite
|
Sign up to set email alerts
|

Studies on apple and blueberry fruit constituents: Do the polyphenols reach the colon after ingestion?

Abstract: The aim of our studies was to determine the amount of polyphenols reaching the colon after oral intake of apple juice and blueberries. After a polyphenol-free diet healthy ileostomy volunteers consumed a polyphenol-rich cloudy apple juice while others consumed anthocyanin-rich blueberries. Ileostomy effluent was collected and polyphenols were identified using HPLC-DAD as well as HPLC-ESI-MS/MS; quantification was performed with HPLC-DAD. Most of the orally administered apple polyphenols were absorbed from or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(128 citation statements)
references
References 32 publications
4
119
0
2
Order By: Relevance
“…In addition, previous work (Aura et al, 2005) suggested that a major portion of ingested polyphenols survive digestion in the upper gastrointestinal tract (GIT) and reach the colon, where they could be subjected to fermentation by colonic microflora. This has been confirmed in human ileostomy patients (Karle et al, 2006). Thus, considering the high catechin content of green tea and cocoa, colonic cells could be exposed to flavanols levels similar to those tested in the present study.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, previous work (Aura et al, 2005) suggested that a major portion of ingested polyphenols survive digestion in the upper gastrointestinal tract (GIT) and reach the colon, where they could be subjected to fermentation by colonic microflora. This has been confirmed in human ileostomy patients (Karle et al, 2006). Thus, considering the high catechin content of green tea and cocoa, colonic cells could be exposed to flavanols levels similar to those tested in the present study.…”
Section: Discussionsupporting
confidence: 86%
“…This observation has been confirmed in human ileostomy patients (29). Therefore, despite the low serum bioavailability of flavonoids (10), due to the high catechin content of green tea, cocoa and other well accepted foodstuffs, colonic cells could be exposed to flavanol levels similar or higher to those tested in the present study.…”
Section: Activation Of Mapks By Ecg Is Required For P53 Stimulation Asupporting
confidence: 76%
“…These phenolic acids are thought to be formed during anthocyanin metabolic processing by enteric bacteria or in chemical reactions [20]. These anthocyanin metabolites have also been found in humans [21][22][23]. It is therefore reasonable to take into account the potential effects of such metabolites when assessing the health benefits of anthocyanins.…”
Section: Absorption and Metabolism And Intake Dosage For Functional Ementioning
confidence: 98%